Development on loan : microcredit and marginalisation in rural China - Loubere, Nicholas (Transforming Asia., 2019)
Key to China's plans to promote rural development is the de-marginalisation of the countryside through the incorporation of rural areas into the urban-based market-oriented financial system. For this reason, Chinese development planners have turned to microcredit - i.e. the provision of small-scale loans to 'financially excluded' rural households - as a means of increasing 'financial consciousness' and facilitating rural de-marginalisation. Drawing on years of in-depth fieldwork in rural China, this book examines the formulation, implementation and outcomes of government-run microcredit programmes in China - illuminating the diverse roles that microcredit plays in local processes of socioeconomic development and the livelihoods of local actors. It details how microcredit facilitates de-marginalisation for some, while simultaneously exacerbating the marginalisation of others; and exposes the ways in which microcredit and other top-down development strategies reflect and reinforce the contradictions and paradoxes implicit in rural China's contemporary development landscape.